A Novel Microfluidic Cell Co-culture Platform for the Study of the Molecular Mechanisms of Parkinson's Disease and Other Synucleinopathies - Fernandes, João T. S.; Chutna, Oldriska; Chu, Virginia; Conde, João P.; Outeiro, Tiago F. (Frontiers in Neuroscience, 2016)
Although the precise molecular mechanisms underlying Parkinson’s disease (PD) are still elusive, it is now known that spreading of alpha-synuclein (aSyn) pathology and neuroinflammation are important players in disease progression. Here, we developed a novel microfluidic cell-culture platform for studying the communication between two different cell populations, a process of critical importance not only in PD but also in many biological processes. The integration of micro-valves in the device enabled us to control fluid routing, cellular microenvironments and to simulate paracrine signaling. As proof of concept, two sets of experiments were designed to show how this platform can be used to investigate specific molecular mechanisms associated with PD. In one experiment, naïve H4 neuroglioma cells were co-cultured with cells expressing aSyn tagged with GFP (aSyn-GFP), to study the release and spreading of the protein. In our experimental set up, we induced the release of the contents of aSyn-GFP producing cells to the medium and monitored the protein’s diffusion. In another experiment, H4 cells were co-cultured with N9 microglial cells to assess the interplay between two cell lines in response to environmental stimuli. Here, we observed an increase in the levels of reactive oxygen species in H4 cells cultured in the presence of activated N9 cells, confirming the cross talk between different cell populations. In summary, the platform developed in this study affords novel opportunities for the study of the molecular mechanisms involved in PD and other neurodegenerative diseases.